"Political Conflict In The Democratic Party: A Case Study Of Post-Munaslub Leadership Dualism In Deli Serdang, North Sumatra" - Dinita Ayu Novela (Jurnal Indonesia Sosial Teknologi, 2023)
This journal broadly discusses one of the recurring issues that often befall political parties, especially in Indonesia, which is political conflict and factionalization. The case study referred to in this context occurs within the internal dynamics of the Democratic Party, particularly after the extraordinary National Congress (Munaslub) held in Deli Serdang, North Sumatra. The theoretical perspectives utilized are political conflict theory and factionalism theory. Political conflict theory, as proposed by Prof. Maswadi Rauf, posits that political conflicts arise from three factors. Firstly, the desire to compete for political positions or power. Secondly, differences in political policies. Thirdly, divergent views on political institutions. Meanwhile, factionalism theory, based on the ideas of Raphael Zariski, defines factions as intra-party groups whose members share the same identity and goals, and they collaborate to achieve those objectives. The research methodology employed is qualitative, supported by in-depth interviews and literature review techniques.